Analysis of the structure of palliative pathology in children of the Voronezh region in 2021 - Yu. Yu. Razuvaeva; V. S. Ledneva; L. V. Ulyanova (Лечащий Врач)
Palliative care for children is a unique and separately developing service from adult palliative care and is aimed at improving the quality of life of a child with severe chronic diseases in which the rehabilitation potential is reduced or absent. The purpose of this study was to analyze the structure of palliative pathology in children of the Voronezh region. The Palliative Pathology Register can be used to accumulate, analyze data, and compile a report on the nosology of palliative pathology in the Voronezh Region. Data were collected from 47 medical institutions of the Voronezh region providing medical care to children: 15 children's polyclinics in Voronezh and Novovoronezh and 32 central district children's hospitals. Data were obtained on the number of children in need of both inpatient and outpatient palliative care, the area of residence, the social status of the family, the main and concomitant diagnoses. The type of nutrition of the child, the type of breathing of the child, the need for additional oxygen therapy, artificial ventilation, psychological and social assistance, information about the type of rehabilitation measures and medications received by the child were also evaluated. Based on the data obtained, it was revealed that directly in the districts of the city of Voronezh, the largest number of palliative patients was detected in the Levoberezhny district. In the Voronezh region, the largest number of patients with palliative pathology is located in the Novousmansky district, which can be attributed to the immediate proximity of the district to the city. According to the structure of the detected palliative pathologies, non-oncological diseases prevail in children of the Voronezh region, which is compared with statistical data for Russia. Also, acquired neurological diseases are most common – cerebral palsy and congenital malformations, in particular brain malformations. Oncological diseases in children, according to our data, occupy a small proportion (4%). In the Voronezh Region, depending on the probability of a fatal outcome, irreversible but not progressive conditions with severe disability and the patient's exposure to complications prevail, which requires the organization of a multidisciplinary approach to palliative therapy, the introduction of new diagnostic methods and rehabilitation measures.